Trio-Based Low-Pass Genome Sequencing Reveals Characteristics and Significance of Rare Copy Number Variants in Prenatal Diagnosis - Chau, Matthew Hoi Kin; Qian, Jicheng; Chen, Zihan; Li, Ying; Zheng, Yu; Tse, Wing Ting; Kwok, Yvonne K.; Leung, Tak Yeung; Dong, Zirui; Choy, Kwong Wai (Frontiers in Genetics, 2021)
Background: Low-pass genome sequencing (GS) detects clinically significant copy number variants (CNVs) in prenatal diagnosis. However, detection at improved resolutions leads to an increase in the number of CNVs, increasing the difficulty of clinical interpretation and management. Methods: Trio-based low-pass GS was performed in 315 pregnancies undergoing invasive testing. Rare CNVs detected in the fetuses were investigated. The characteristics of rare CNVs were described and compared to curated CNVs in other studies. Results: 603 rare CNVs including 597 constitutional and six mosaic CNVs were detected in 272 fetuses (272/315, 86.3%), providing 1.9 rare CNVs per fetus (603/315). Most CNVs were smaller than 1Mb (562/603, 93.2%), while 1% (6/603) were mosaic. 46 de novo (7.6%, 46/603) CNVs were detected in 11.4% (36/315) cases. 84 CNVs (74 fetuses, 23.5%) involved disease-causing genes of which the mode of inheritance was crucial for interpretation and assessment of recurrence risk. Overall, 31 pathogenic/likely pathogenic CNVs were detected, among which 25.8% (8/31) were small (<100kb; n=3) or mosaic CNVs (n=5) . Conclusions: We examined the landscape of rare CNVs with parental inheritance assignment and demonstrated that they occur frequently in prenatal diagnosis. This information has clinical implications regarding genetic counseling and consideration for trio-based CNV analysis.